1962
DOI: 10.1149/1.2425442
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of the Tantalum and Tungsten Borides

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1966
1966
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Moreover, the activation energy was determined for the temperature range of 1400-1900 • C, which is consistent with the microstructure evolution under discussion (2000 • C). Leitnaker et al 72 suggested that the heat of formation of TaB was 160 kJ/mol, whereas other borides, including TaB 2 , should have the heat of formations between 160 and 270 kJ/mol. The results of the numerical simulation of the growth process for Ta 3 B 4 are presented in Figure 9 (see Section S5 and video files for details).…”
Section: 33mentioning
confidence: 99%
“…Moreover, the activation energy was determined for the temperature range of 1400-1900 • C, which is consistent with the microstructure evolution under discussion (2000 • C). Leitnaker et al 72 suggested that the heat of formation of TaB was 160 kJ/mol, whereas other borides, including TaB 2 , should have the heat of formations between 160 and 270 kJ/mol. The results of the numerical simulation of the growth process for Ta 3 B 4 are presented in Figure 9 (see Section S5 and video files for details).…”
Section: 33mentioning
confidence: 99%
“…In treatments (3), (4), and (5) , the heat of formation is calculated assuming the boride phas e to be nonstoichiometric, however, an equivalent result is obtained if we assume the aluminum boride to be stoichiometric but accompanied by an e xcess of elemental boron. With the application of a correction for this excess , th e c alculation of the heats of formation of the stoichiometric and nonstoichiometric formulas become identical.…”
Section: Analysis Of Combustion Residuesmentioning
confidence: 99%
“…As there is no relevant data on the phase of TaB in FactSage database, the Gibbs free energy change curve of TaB generated by Ta and B reaction cannot be calculated by FactSage. Therefore, CrB is used to judge the difficulty of the reaction between Ta and B, which has the same crystal structure with TaB 31–33 . Therefore, in the initial stage of high‐energy ball milling, solute tantalum tends to dissolve carbon atoms first, followed by nitrogen atoms, and then boron atoms 34 .…”
Section: Resultsmentioning
confidence: 99%